Käyttöliittymä vaaleihin Tutkimus vaalikoneista kansalaisten, ehdokkaiden ja journalismin näkökulmista - Borg, Sami (Tampere University Press, 2020)
" Voting advice applications (VAA) have supported Finnish voters for over 20 years in their voting decisions in general elections. Most Finnish VAAs are planned and provided by the media, and they are based on matching opinions of individual candidates with an individual VAA users before elections. Nowadays, in Finland, VAAs are important for almost all age groups. Among the youngest voters VAAs are viewed as the most important source of information to support voting decisions. The book provides up-to-date and comprehensive picture over the role and significance of VAAs in the Finnish political system and in the political communication arena. Research topics deal also with VAA journalism and how candidates perceive VAAs. Research data and data materials in use are wide-ranging. They range from survey data sets to questions of VAAs and from interviews of candidates and VAA producers to media content about VAAs. Theoretical research questions are mostly related to the democratic value of VAAs. This perspective is central also in the end of the book, which opens possible future pathways for the VAAs."